A LOOK AT THE POLITICAL THOUGHT OF AMIR TEMUR (INTERPRETED BY MARGA DE TILLY) - Israilov Nodir Rahimjonovich (Sciental Journals Publishing, 2025)
The article examines the history of the early period of Amir Temur's statehood in the work of the 18th-century French historian Marguerite de Tilly, entitled “The History of Tamerlane, Emperor of the Mongols and Conqueror of Asia”. The French orientalist's observations on the relationship between Amir Husayn and Amir Temur in the struggle for control of Transoxiana are analyzed based on sources from the Timurid period. The study uses comparative analysis and problem-chronological methods. The French orientalist’s observations on Amir Temur’s strategic struggle with Tughluq Temur Khan for the formation of a centralized state are examined based on sources, and errors and shortcomings are discussed.
Keywords: Amir Kazaganbek, Amir Abdullah, Bayonkulihan, Tughluq Temurkhan, Amir Hussein, Hadji Barlos, Amir Temur, Ilyashkhoja, Sharafiddin Ali Yazdi, Ibn Arabshah, Marga de Tilly, Movarounnahr, Mogolistan.